INTERNAL CONTROL AS A TOOL OF SUPPORT ECONOMIC SECURITY OF THE ORGANIZATION AT THE MICRO LEVEL - O. A. Ageeva; Yu. D. Matytsyna (Вестник университета)
Internal control is an integral part of an organization’s economic security. The purpose of the study is to determine the internal control tools that allow you to ensure and maintain a sufficient level of economic security of the enterprise. The subject is the internal control system, which is used to identify external and internal threats to the economic security of an economic entity at the micro level. The research methodology is based on the collection and generalization of facts related to the subject under study, the formation of a hypothesis about the subject of research – the Internal Control System (ICS) – and the development of a general idea of ways to overcome existing threats. As a result, the authors made a conclusion about the effectiveness of the internal control system in the enterprise in order to ensure its economic security.